Analysis of the Content of the Sixth-Grade Science Book in Elementary School in Lighting the Twenty-First-Century Skills - Areej Alfaifi (Umm Al-Qura University, 2023)
This study aimed to analyze the sixth-grade science book in the elementary school examining the twenty-first-century skills, the researcher used the descriptive analytical approach by preparing an analysis tool that was applied to the study sample, which is the sixth-grade science book in the first and second semester. and there are several skills under each of these main areas as follows: learning and innovation skills (creativity and innovation, communication and cooperation, critical thinking and problem solving), information culture and technology skills (communication and media culture, information culture, in-formation technology culture), career and life skills (adaptation and flexibility, initiative and self-direction, personal and societal responsibility). The results of the study were as follows: The education and innovation skills got the highest percentage, which is %64 in the first semester and %63.4 in the second semester. The career and life skills were in the second with a percentage of %25.1 in the first semester and %25.3 in the second semester. The information culture and technology skills were in the third that is %10.8 in the first semester and %11.3 in the second semester, and in light of the results it reached. The research presented a set of recommendations and suggestions.